Toxicological assessment of electronic cigarette vaping: an emerging threat to force health, readiness and resilience in the U.S. Army. (3rd September 2022) - Williams, Marc A.; Reddy, Gunda; Quinn, Michael J.; Millikan Bell, Amy
Abstract: The U.S. Army and U. S. Army Public Health Center are dedicated to protecting the health, and readiness of Department of the Army Service Members, civilians, and contractors. Despite implementation of health programs, policies and tobacco control interventions, the advent of electronic nicotine delivery systems (ENDS), including electronic cigarettes (e-cigs), represent unregulated and poorly defined systems to supplant or substitute use of conventional nicotine products (e.g., cigarettes and pipe tobacco). E-cigs present unique challenges to healthcare officials vested in preventive medicine. The health impact of an e-cig and vaping on an individual's acute or chronic disease susceptibility, performance and wellness, is fraught with uncertainty. Given the relatively recent emergence of e-cigs, high-quality epidemiological studies, and applied biological research studies are severely lacking. In sparsely available epidemiological studies of short-term cardiovascular and respiratory health outcomes, any attempt at addressing the etiology of acute and chronic health conditions from e-cig use faces incredible challenges. Until relatively recently, this was complicated by an absent national regulatory framework and health agency guidance on the manufacture, distribution, selling and use of e-cigs or similar ENDS devices and their chemical constituents. Two key issues underpin public health concern from e-cig use: 1) continued or emergent nicotine addiction and potential use of these devices for vaping controlled substances; and 2) inadvertent sudden-onset or chronic health effects from inhalational exposure to low levels of complex chemical toxicants from e-cig use and vaping the liquid. Herein, the health impacts from e-cig vaping and research supporting such effects are discussed.